Juristische Netzwerkforschung Modellierung, Quantifizierung und Visualisierung relationaler Daten im Recht - Coupette, Corinna (Mohr Siebeck, 2019)
Legal network science explores how legal phenomena can be represented as networks and investigates what can be gained from their quantification and visualization. Corinna Coupette introduces legal network science to the German legal discourse. Based on an original dataset of decisions by Germany's Federal Constitutional Court, she develops tools for modeling, measuring, and mapping the law.The work includes an online appendix, which is freely available at :https://doi.org/10.1628/978-3-16-157012-4-appendix